Qumran between the Old and New Testaments - Cryer, Frederick H.; Thompson, Thomas L., 1939- (Journal for the study of the Old Testament. Supplement series, 1998)
Papers from the International Scandinavian Conference on the Dead Sea Scrolls and Qumran, sponsored by the University of Copenhagen and held in 1995. In addition to the contributions of Florentino Garc'a Mart'nez, Emanuel Tov and Ben Zion Wacholder, this collection offers a wide range of recent Scandinavian scholarship on the Dead Sea Scrolls. Central issues dealt with include the dating of the scrolls, the theological relationships between the Scrolls and the Old Testament, questions relating to text and tradition formation, and the social relations between Qumran and contemporary Jewish sect.